Social Practices of PKH in Padang - Eddie, Randrianiaina Jaona; Azwar, Azwar; Zamzami, Lucky; Erica, Rasoa Totonantenaina (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
From 2022 to 2024, Padang was the city with the highest number of PKH participants (KPM) in West Sumatra Province. The success of the PKH program is indicated by the number of KPM who achieve independent graduation. However, in 2024, Padang only managed to graduate 157 KPM, equivalent to 0.65% of 23,967 KPM. The purpose of this research is to analyze the social practices of KPM in Padang using Anthony Giddens' structuration theory. The data in this study were collected through in-depth interviews, observations, and document studies. A total of 17 informants participated in this study, consisting of 11 key informants and 6 observer informants. The study found that the perceptions of KPM in Padang regarding PKH assistance included multiple perspectives: PKH as a Conditional Cash Transfer (CCT) assistance, as an opportunity, as assistance funds, as a regular assistance, and PKH as restricted funds. The KPM in Padang utilized PKH assistance by: (1) meeting their children's educational needs; (2) supporting pregnant mothers, toddlers, and the elderly; (3) covering daily necessities; and (4) saving. The barriers that prevent the KPM in Padang from achieving independent graduation include the lack of business opportunities, low economic conditions, aid dependency, mindset, uncontrollable behavior of KPM, and misdirected assistance. These findings highlight the structuration dynamics in the implementation of the PKH Program, where the independent graduation process cannot be understood merely as an individual decision or behavioral issue, but is shaped by the dynamic interaction between agents (KPM) and the surrounding structural conditions.